Thermal Degradation Behavior and Kinetics of Polybenzoxazine Based on Bisphenol-S and Allylamine. Issue 4 (2nd April 2016) - Huang, Jinbai; Yue, Hu; Lv, Shufang; Hao, Zhanzhan; Wang, Man; Liu, Yanfang
ABSTRACT: The thermal degradation behavior of polybenzoxazine based on bisphenol-S/allylamine was studied by Fourier transform–infrared spectroscopy and thermogravimetry–mass spectrometry. The reaction proceeded through detaching of Schiff bases and cleavage of aromatic C–S bonds and the Mannich bridge structures; the scission temperature of the aromatic C–S bond was lower than those of C–N and C–C bonds. The activation energy of the thermal degradation was evaluated with the Flynn–Wall–Ozawa method.